Shear connection system and performance evaluation of FRP-concrete composite deck - Cho, Keunhee; Park, Sung Yong; Kim, Sung Tae; Cho, Jeong-Rae; Kim, Byung-Suk (KSCE journal of civil engineering, 2010)
Strong composition between FRP and concrete is an indispensable prerequisite to achieve the structural integrity of FRP-concrete composite deck. Accordingly, this study evaluates experimentally the behavioral characteristics of such shear connection systems realized by coarse sand coating and concrete wedge. The results show that coarse sand coating develops composite performance close to perfect composition in the shear direction but exhibits weakness against normal split. On the other hand, concrete wedge appears to be an efficient solution to resolve such problem. Therefore, a new shear connection system combining coarse sand coating and concrete wedge has been conceived and test revealed that the new shear connection system provides equivalent static performance together with significantly improved fatigue performance compared to the coarse sand coating composition. Following, the shear connection system combining both coarse sand coating and concrete wedge constitutes an efficient solution satisfying the strong composition requirement for the structural system.